CHARACTERIZATION OF Enterobacter Spp. ISOLATED FROM THE GUT OF RICE WEEVIL - A. Abubakar; Abdullahi. Y; G. G. Memi; S. Mohammed (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2018)
Rice weevil is the most widely distributed and destructive insect pest found in cereal products. The insects usually harbour some biologically important bacteria in their guts which may considerably affect various aspects of their ecology, behaviour, and physiology. The aim of this research was to characterize the Enterobacter sp. previously isolated from rice weevil and identified molecularly. These bacteria was investigated based on (i) morphological properties: (ii) biochemical; its ability to utilize different type of carbon and nitrogen sources (glucose, sucrose, lactose, starch, casamino acid, nitrate, nitrite and ammonium), (iii) tolerance towards various heavy metal ions (copper, zinc, manganese, aluminium) and antibiotics. This Enterobacter sp. was found to be Gram negative, rod-shaped, non-motile bacterium, and showed positive reaction with catalase, urease and citrate. Based on carbon and nitrogen experiments, sucrose and casamino acid were found to be suitable carbon and nitrogen source for the growth of Enterobacter sp. The isolate was also tolerant to aluminium with maximum tolerance concentration of 800 mg/L with growth rate (μ) of 0.240 h-1. Besides that, this bacterium was able to grow in 400 mg/L of copper and exhibit intolerance towards zinc at concentration of 200 mg/L to 800 mg/L. In addition, the isolate was able to tolerate well up to 800 mg/L (growth rate: 0.244 h-1) of manganese. The bacterium was also found resistant to erythromycin, chloramphenicol and ampicillin. Considering the ability of the bacteria to tolerate various types of heavy metals, they could potentially be used for bioremediation of heavy metal from environment